2011
DOI: 10.1098/rsif.2011.0586
|View full text |Cite
|
Sign up to set email alerts
|

Modulating protein adsorption onto hydroxyapatite particles using different amino acid treatments

Abstract: Hydroxyapatite (HA) is a material of choice for bone grafts owing to its chemical and structural similarities to the mineral phase of hard tissues. The combination of osteogenic proteins with HA materials that carry and deliver the proteins to the bone-defective areas will accelerate bone regeneration. The study investigated the treatment of HA particles with different amino acids such as serine (Ser), asparagine (Asn), aspartic acid (Asp) and arginine (Arg) to enhance the adsorption ability of HA carrier for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 40 publications
4
78
0
Order By: Relevance
“…To our knowledge, attention has been focused on the amount of adsorption for large biomolecules, while models of adsorption onto MHA have scarcely been mentioned in the previous papers. Wassell et al found that biomolecule adsorption behavior on traditional hydroxyapatite particles fitted with the Langmuir model [23], and Lee et al drew a conclusion that bovine serum albumin (BSA) and lysozyme adsorption onto amino acidfunctionalized hydroxyapatite particles fitted better into the Freundlich model than the Langmuir model [22]. However, whether biomolecule adsorption on MHA exhibits similar behavior has not been reported.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…To our knowledge, attention has been focused on the amount of adsorption for large biomolecules, while models of adsorption onto MHA have scarcely been mentioned in the previous papers. Wassell et al found that biomolecule adsorption behavior on traditional hydroxyapatite particles fitted with the Langmuir model [23], and Lee et al drew a conclusion that bovine serum albumin (BSA) and lysozyme adsorption onto amino acidfunctionalized hydroxyapatite particles fitted better into the Freundlich model than the Langmuir model [22]. However, whether biomolecule adsorption on MHA exhibits similar behavior has not been reported.…”
Section: Introductionmentioning
confidence: 95%
“…The adsorption behaviors of large biomolecules onto hydroxyapatite have been frequently studied [16,17,19,22]. To our knowledge, attention has been focused on the amount of adsorption for large biomolecules, while models of adsorption onto MHA have scarcely been mentioned in the previous papers.…”
Section: Introductionmentioning
confidence: 99%
“…The electrical charge of the adsorbing surface can also affect adsorption as it determines electrostatic forces between proteins and surface. Such forces were for example found to govern adsorption of BSA onto functionalized hydroxyapatite particles [12]. Therefore the electrochemical conditions are supposed to influence protein adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Acidic amino acids (e.g., aspartic or glutamic acids) lead to a negatively charged surface that is ideal for the selective uptake of positive charged LSM. By contrast, basic amino acids (e.g., arginine) enhance the adsorption of negative charged proteins such as bovine serum albumin [142]. In the same way, organic compounds like mercaptosuccinic acid and citric acid were employed to increase the uptake of cytochrome C [143] and LSM [144], respectively.…”
Section: Protein Adsorption and Release From Hap Nanoparticlesmentioning
confidence: 99%